Zhuangzi’s Theory of Freedom: Considerations and Reference for Executive Studies - Huy, Pham Quang (VNU Journal of Science: Legal Studies; Vol 35 No 3, 2019)
On the basis of the presentation, analyzing the free doctrine of Zhuang Zhi, the author explains the origin and the rationale for this doctrine as well as the nature of Zhuang Zhi's free philosophy. At the same time, the author also refers to the philosophy of freedom with the doctrine of the rule of law, especially the content of executive limitation to freedom.